Geospatial analysis applied to epidemiological studies of dengue: a systematic review - Maria Aparecida de Oliveira; Helena Ribeiro; Carlos Castillo-Salgado (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
A systematic review of the geospatial analysis methods used in the dengue fever studies published between January 2001 and March 2011 was undertaken. In accordance with specific selection criteria thirty-five studies were selected for inclusion in the review. The aim was to assess the types of spatial methods that have been used to analyze dengue transmission. We found twenty-one different methods that had been used in dengue fever epidemiological studies in that period, three of which were most frequently used. The results show that few articles had applied spatial analysis methods in dengue fever studies; however, whenever they were applied they contributed to a better understanding of dengue fever geospatial diffusion.